2005
DOI: 10.1116/1.2110387
|View full text |Cite
|
Sign up to set email alerts
|

Thermal reaction of polycrystalline SiC with XeF2

Abstract: Studies on the thermal reaction behavior of polycrystalline cubic silicon carbide (SiC) with effusive xenon difluoride (XeF2) have been carried out over the sample temperature (Ts) range from 300to900K using molecular beam quadrupole mass spectrometry combined with a time-of-flight technique and ex situ surface analyses, i.e., x-ray photoelectron spectroscopy (XPS) and scanning Auger microscopy (SAM). Above Ts=700K, the reaction product desorbed from the SiC surface was identified as SiF4. The flux intensity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This signal is probably typical of the anchoring part. Such a low-energy position of C 1s is very specific and considered as an unambiguous indication of Si−C bonding. Similar low-energy positions for the C 1s peak are reported on alkyl-terminated silicon surfaces . Therefore, our XPS results demonstrate that Si−C bonds are present at the buried interface.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This signal is probably typical of the anchoring part. Such a low-energy position of C 1s is very specific and considered as an unambiguous indication of Si−C bonding. Similar low-energy positions for the C 1s peak are reported on alkyl-terminated silicon surfaces . Therefore, our XPS results demonstrate that Si−C bonds are present at the buried interface.…”
Section: Resultssupporting
confidence: 83%
“…At the last stages of layer abrasion corresponding to the unique and specific low-binding-energy C 1s position (Figure , curve c), the Si 2p spectrum can be fitted with only two spin−orbit doublets (Figure a); one centered at 99.3 eV associated with bulk Si and the other one at 99.8−99.9 eV related to the Si/polymer interface (here and below the energies given are those of the 2p 3/2 line maximum). At this ultimate stage of polymer profiling, O and X signals are missing, which is plausibly due to higher sputtering yields for O and X as compared to those for C. The Si 2p contribution associated with a bulk SiC phase would appear at 100.4 eV, as compared to 99.3 eV for bulk Si. However, for alkyl-terminated Si the chemical shift of Si 2p may be as low as 0.2−0.3 eV .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to CVD graphene on SiO 2 , epitaxial graphene on SiC has better surface quality and thus is suitable for STM imaging. However, SiC can react with injected XeF 2 gas, making the analysis of graphene using XPS more ambiguous, while SiO 2 substrate is more inert to fluorination 17 35 . Thus, CVD graphene was mainly used in fluorination experiment followed by spectroscopic analysis and epitaxial graphene was used for STM imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Watanabe et al have reported on the thermal reaction of polycrystalline SiC with XeF 2 vapor. 23,24) However, there are few reports on the XeF 2 plasma etching process for the microfabrication of SiC. Therefore, we also propose a XeF 2 plasma etching process for the microfabrication of SiC.…”
Section: Introductionmentioning
confidence: 98%